Korelasi Media Dan Sumber Pembelajaran Dalam Implementasi Kurikulum Merdeka - Mila Mahmudah (PROGRESSA: Journal of Islamic Religious Instruction, 2022)
The independent curriculum is a simpler and more in-depth curriculum that focuses on essential material and the development of student competencies in its phases. Deep learning is unhurried and fun. Learning through project activities provides broad opportunities for educators and students to explore and discuss actual materials and issues such as the environment, health, technology and others so as to develop the potential character of students. In implementing an independent curriculum, of course, media and learning resources are an important part. Because with relevant learning resources and learning media, it is possible for educational units to optimize the selection of an independent curriculum in the educational process. Educators and learning media are interrelated to provide easy learning for students. Individual attention and guidance can be carried out by educators properly while information can be presented clearly, interestingly and thoroughly by media and learning resources.